Cannabidiol use in patients with Dravet syndrome and Lennox-Gastaut syndrome: experts' opinions using a nominal group technique (NGT) approach. (24th March 2023) - Bonanni, Paolo; Ragona, Francesca; Fusco, Carlo; Gambardella, Antonio; Operto, Francesca Felicia; Parmeggiani, Lucio; Sartori, Stefano; Specchio, Nicola
ABSTRACT: Background: Dravet syndrome (DS) and Lennox-Gastaut syndrome (LGS) currently present a therapeutic challenge. A pharmaceutical cannabidiol (CBD) specialty (Epidyolex®) has been approved by the FDA and EMA for the treatment of seizures in these syndromes. However, in Italy, the use of galenic formulations versus the pharmaceutical CBD has not been clearly regulated. Aim: To share and disseminate expert' opinions on how to use and administer pharmaceutical CBD in patients with DS and LGS as well as identifying a possible strategy for the switch from galenic to pharmaceutical specialty. Methods: A nominal group technique (NGT) was used, involving eight Italian adult and pediatric neurologists. Two questionnaires were consecutively administered and the Clinician' responses were discussed in a final meeting in order to draw the own conclusions. Results: The use of a pharmaceutical CBD is considered preferable to galenic formulations, in terms of reproducibility, safety, and control of the delivered dose. Conclusion: The use of a pharmaceutical CBD in DS and LGS patients is useful for both seizure treatment and quality of life (QoL) improvement. However, further studies are needed to confirm the improvement in QoL and the best strategy for switching from a galenic formulation to pharmaceutical CBD.